ANALISIS RASIO KEUANGAN DALAM MERENCANAKAN PERTUMBUHAN LABA : PERSPEKTIF TEORI SIGNAL - ANDRIANTO PURNOMO WIJAYA, ANDRIANTO PURNOMO WIJAYA ANDRIANTO PURNOMO WIJAYA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This study aimed to examine the effect of financial ratio analysis consisting of the liquidity ratio, solvability ratios, activity ratios, profitability ratios and earnings growth as well as to examine the role of financial ratios in planning for future earnings growth. This study uses secondary data the number of samples used is 110 companies included in the manufacturing, agriculture, mining, and trade are listed on the Indonesia Stock Exchange and profit growth from 2009 to 2010. Other secondary sources of data in the form of its 12 sub-sectors of the industry that have the financial statements starting from the year 1991 to 2010. Results of this study indicate that financial ratios significant effect on earnings growth, however, these ratios are not able to predict the exact profit growth in the future. In the perspective of signaling theory, earnings growth cannot be captured by the market as a signal in the assessment of the future prospects of the company.